Formation of a Generalized System of Indicators of Regional Economic Security - L. P. Bakumenko; N. S. Vasileva (Статистика и экономика)
The purpose of the study. The purpose of the study is to model a generalized system of indicators of economic security of the regions of the Russian Federation. The topic of the study is relevant, since the prevention of crisis situations, the organization of stable functioning of regional economies, the development of territories and the growth of the standard of living of the population necessitate constant monitoring of the economic security of the regions of Russia, which is based on the modeling of a system of indicators, because socioeconomic development is a complex system of interconnections, various components of the economy.Data and methods. The normative and legal documents of the government bodies of the Russian Federation, official data of the Federal State Statistics Service, the Unified Interdepartmental Information and Statistical System and the Ministry of Finance of the Russian Federation were used as the information and empirical base of the study. The indicators were selected based on the works of Russian scientists and Decree of the President of the Russian Federation dated May 13, 2017 No. 208 “On the Strategy of Economic Security of the Russian Federation for the period up to 2030”. The method of factor analysis - principal component analysis was used in the formation and modeling of a generalized system of indicators of economic security of regions.Solutions and results. To achieve this goal, at the initial stage of the study, a system of indicators was formed, consisting of 26 indicators characterizing the production, financial, social and other aspects of the life of the regions that determine economic security. The information compression method, the principal component analysis, were applied to the selected indicator system. When choosing the number of principal components (factors), we relied on the eigenvalues of the principal components (Kaiser Criterion) and their contribution to the overall variance of the initial features. Seven principal components were identified. At the same time, their total contribution to the total variance was 78.45%, which is a sufficient condition for the formation of components. The best interpretation of the principal components was achieved without subjecting factor loads to any rotations. Thus, the components were obtained: f_1 (financial security), f_2 (demographic security), f_3 (social security), f_4 (food security), f_5 (scientific and technical security), f_6 (degree of depreciation of fixed assets), f_7 (industrial safety). The information content coefficients for all principal components are in the range from 0.70 to 0.95; therefore, their composition is significant. The constructed regression model in a standardized form made it possible to determine the impact of the selected generalized factors on the level of economic security of the regions of the Russian Federation.Conclusion. Having a high level of economic security is important for the activities of each region, therefore it is necessary to conduct high-quality monitoring of the degree of economic security, which allows you to identify weaknesses and strengths in the economy. The results of the study made it possible to form the main generalized factors of economic security of the regions: financial, demographic, social, food, scientific and technical, industrial safety and the degree of depreciation of fixed assets - the subjects of the Russian Federation can be assessed from the point of view of their economic stability, and, consequently, their competitiveness at the national level.